Synthesis of Novel Azides and Triazoles on the Basis of 1Ð½-Pyrazole-3-Carboxylic Acids - Dalinger, Aleksander I; Medved'ko, Alexey V; Balalaeva, Alexandra I; Vatsadze, Irina Ð; Dalinger, Igor L; Vatsadze, Sergey Z (Chemistry of heterocyclic compounds (New York, N.Y. 1965), 2020)
The goal of this work was to obtain novel ligands basedis on 1H-pyrazole-3(5)-carboxylic acids containing the triazole moiety at positions 3(6) or 4. Another goal was to study the possibility of joining pyrazole carboxylic acid fragments with various framework structures to create polychelated ligands that can be used in medicinal chemistry and metal complex catalysis. Methods have been developed for the synthesis of previously unknown N-unsubstituted 5- and 4-azido-1H-pyrazole-3-carboxylic acids from the corresponding available amino derivatives in high yields. For the first time, the joining of bispidines to azoles was carried out using the copper-catalyzed [3+2] cycloaddition reaction.